A Scale for E-Content Preparation Skills: Development, Validity and Reliability - Tekin, Ahmet; Polat, Ebru (Ani Yayincilik, 2016)
Problem Statement: For an effective teaching and learning process it is critical to provide support for teachers in the development of e-content, and teachers should play an active role in this development. Purpose of the Study: The purpose of this study is to develop a valid and reliable Likert-type scale that will determine pre-service teachers' econtent preparation skills according to the criteria determined by the Ministry of Education. The scale developed over the course this study is intended for use not only by pre-service teachers but also in-service teachers to determine their e-content preparation skills. Method: The purposeful sampling method was employed to select participants. For exploratory factor analysis, participants consisted of 226 pre-service teachers from the Department of Computer and Instructional Technologies at a state university located in eastern part of Turkey. In addition, 588 teacher candidates were randomly selected for confirmatory factor analysis. When analyzing the scale's validity and reliability, respectively, convenience according to factor analysis, item analysis, exploratory factor analysis, Cronbach's alpha and split-half value calculation was applied. Findings: The validity and reliability tests of the scale, which were developed in accordance with the criteria of e-content published by MEB, were performed on teacher candidates. Experts inspected the draft scale prepared during the validity study, and the items that were identified as inappropriate and damaging to the appearance of validity were extracted. According to factor analysis, those items with a load value of less than 0.45 and items with a high load value in two items were extracted from the draft scale. The scale showed a seven-factor structure after repeated exploratory factor analysis; these seven factors provided an explained variance for 74.23% of the scale. Considering the acceptable levels of goodness for fit indexes acquired by confirmatory factor analysis, we can conclude that the seven-factor construct based on exploratory factor analysis results was confirmed. The internal consistency coefficient (Cronbach's alpha) was determined as 0.98. The analyzed item total correlation changes between 0.52 and 0.80. Conclusion and recommendations: In conclusion, the survey items possess high reliability to evaluate the same behavior based on the gathered data.
Keywords: E-Content; Pre-Service Teachers; Validity and Reliability; E-Content Preparation Skill